IMPACT OF AGROMETEOROLOGICAL CONDITIONS TO CHANGE OF PROPERTIES OF THE RECLAIMED SOLONETZES IN THE DRY STEPPE ZONE - I. Lyubimova; A. Aksenov; A. Gorobets (Бюллетень Почвенного института им. В.В. Докучаева, 2010)
Estimation of the impact of weather conditions on the change in the content of readily soluble salts and metabolic bases and humus in the reclaimed automorphic high-carbonate solonetzes of the dry-steppe zone at different of types of meliorative effects. The given results of researches show that weather conditions first of all render effects on rapidly changing soil properties, such as readily soluble salt content and exchangeable elements. There is no evidence of reliable correlations between humus content and weather conditions. Directionality and the share of the impact of climate indicators on different properties of reclaimed solonetzes is different, but in most cases it's is less than 30% of the share of influence of other factors.